Flecainide Toxicity Leading to Loss of Pacemaker Capture and Cardiac Arrest - Rivner, Harold (JACC Case Rep, 2021)
An 86-year-old man with paroxysmal atrial fibrillation on flecainide, a class IC antiarrhythmic, presented with cardiac arrest. The patient had extremely wide QRS complexes with inconsistent pacemaker capture on electrocardiography. Due to cardiac failure and renal failure, the patient developed progressive flecainide toxicity, which led to pacemaker failure, and ultimately, death. (Level of Difficulty: Beginner.)